Enhancement of CO2 trapping efficiency in heterogeneous reservoirs by water‐alternating gas injection. Issue 5 (22nd July 2018) - Al‐Khdheeawi, Emad A.; Vialle, Stephanie; Barifcani, Ahmed; Sarmadivaleh, Mohammad; Iglauer, Stefan
Abstract: Carbon geosequestration efficiency is affected by various factors including reservoir heterogeneity, caprock properties, rock wettability, aquifer brine salinity and injection‐well configuration. Some parameters (e.g. the formation geology) cannot be changed but it is possible to select others and engineer an optimized storage program. One of these parameters is the way CO2 is injected into the reservoir. There are three main options for this: (1) continuous injection, (2) intermittent injection, and (3) water‐alternating gas (WAG) injection. We thus studied the efficiency of each injection option and predicted the associated storage capacities and CO2 ‐plume movements (which are related to the containment security). We found that WAG injection showed significantly superior behavior over continuous and intermittent injections (which resulted in similar CO2 flow responses). Specifically, residual and solubility trapping were significantly enhanced, whereas vertical CO2 migration was cut by approximately two‐thirds. Thus, in the examined reservoir, the WAG injection is preferred as it strongly enhances CO2 storage efficiency and containment security. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd.